RELATIONSHIP BETWEEN MANAGERS’ POLITICAL BEHAVIOR IN PERFORMANCE APPRAISAL SYSTEMS AND PERSONAL OUTCOMES - Ismail, Azman; Mohd Raduan, Nur Safina (Jurnal Manajemen dan Kewirausahaan, 2013)
This study was undertaken to investigate the correlation between managers’ political behavior in performance appraisal systems and personal outcomes using self-reported questionnaires gathered from employees who have worked in a defence based university, Malaysia. The outcomes of stepwise regression analysis showed that motivational and punishment motives did act as important determinants of job satisfaction, but motivational and punishment motives did not act as important determinants of job turnover in the organizational sample. This study further provides discussion, implications and conclusion.